Relationship Between Behavior and COVID-19 Transmission Prevention at Kendari Beach, Kendari City, Indonesia - Nur Malisa; Asriati Asriati (Journal of Epidemiology and Health Science, 2024)
Background: Efforts to prevent the spread of the virus and mitigate the impact of the pandemic require more than just government action; they also necessitate active involvement from all community members. The active participation of every individual is crucial for effective pandemic control. By engaging all parties, it is hoped that the pandemic can be managed more effectively. Objective: This study aimed to analyze the relationship between behavior and preventive efforts against COVID-19 transmission among visitors to Kendari Beach, Kendari City, in 2020. Methods: The study was conducted at Kendari Beach, Kendari City, from February to March 2021. It utilized an analytic observational design with a cross-sectional study approach. The population comprised all visitors to Kendari Beach, estimated to be around 200-300 people per day. The sample was drawn from visitors present during the research period. Data analysis involved descriptive statistics and chi-square tests to determine the relationship between variables. Results: The study revealed a strong relationship between knowledge, attitudes, and practices with preventive efforts against COVID-19 transmission among visitors to Kendari Beach, Kendari City. Conclusion: The study concluded that visitor behavior is strongly related to the implementation of COVID-19 health protocols at Kendari Beach. Therefore, it is recommended that the community continues to adhere to health protocols during the COVID-19 pandemic to reduce the incidence of illness and death caused by the virus. Keywords: behavior, prevention, COVID-19, Kendari, Indonesia